Manajemen Emosi dalam Dimensi Komunikasi Antarpribadi - Rizqi Pratama Putra; Atie Rachmiatie (Bandung Conference Series: Public Relations, 2023)
Abstract. Interpersonal communication is a technique for communicators to convey messages to recipients with specific goals, such as changing the communicant's perception or influencing attitudes or behavior. One of the special schools in the Kiaracondong area, SLB C Sukapura is dedicated to educating students with disabilities. The theory used is action assembly published by John Greene in 1984 and the theory put forward by Daniel Goleman about emotional intelligence. The purpose of this research is to understand more deeply about managing emotions. The method used by researchers is a qualitative research method with a phenomenological study approach and based on the experience of informants obtained from in-depth interviews, observation and documentation. The results of this study are first, the teacher's motives for students with special needs in an effort to manage emotions, namely to shape the attitudes and behavior of students in social activities so that they are not easily provoked by emotions if they feel uncomfortable. Second, managing the teacher's emotions because students will imitate all the behavior and attitudes of the teacher in all things, if the teacher is easily provoked by his emotions, then the success of the teacher's motives in managing the emotions of his students will not be achieved. Third, the meaning obtained by a teacher in an effort to manage student emotions depends on the experience and perspective of the individual teacher. Fourth, the calmness of the teacher is an important aspect in the successful management of student emotions, students' anxiety will arise if they feel uncomfortable in their surroundings. Abstrak. Komunikasi antar pribadi adalah teknik bagi komunikator untuk menyampaikan pesan kepada penerima dengan tujuan tertentu, seperti mengubah persepsi komunikan atau mempengaruhi sikap maupun perilaku. Salah satu sekolah luar biasa di daerah Kiaracondong, SLB C Sukapura didedikasikan untuk mendidik murid-murid yang memiliki kelainan. Teori yang digunakan yaitu action assembly yang dipublikasikan oleh John Greene pada tahun 1984 dan teori yang dikemukakan oleh Daniel Goleman tentang kecerdasan emosional. Tujuan penelitian ini yaitu memahami lebih dalam tentang pengelolaan emosi. Metode yang digunakan peneliti yaitu metode penelitian kualitatif dengan pendekatan studi fenomenologi dan berdasarkan dengan pengalaman narasumber yang diperoleh dari wawancara mendalam, observasi dan juga dokumentasi. Hasil dari penelitian ini adalah pertama, motif guru terhadap murid berkebutuhan khusus dalam upaya mengelola emosi yaitu membentuk sikap dan perilaku murid dalam kegiatan bersosialisasi agar tidak mudah terpancing emosi jika merasa tidak nyaman. Kedua pengelolaan emosi guru karena murid akan meniru seluruh perilaku dan sikap guru dalam segala hal, jika guru mudah terpancing emosinya maka keberhasilan dari motif guru dalam mengelola emosi muridnya tidak akan tercapai. Ketiga, makna yang diperoleh seorang guru dalam upaya pengelolaan emosi murid tergantung pada pengalaman dan perspektif individu guru. Keempat, ketenangan guru menjadi aspek penting dalam keberhasilan pengelolaan emosi murid, kegelisahan murid akan timbul jika sedang merasa tidak nyaman berada di lingkungan sekitarnya.